PEMIKIRAN FILOSOFIS YANG MENDASARI PEMELIHARAAN LINGKUNGAN HIDUP: STUDI KASUS BANJIR DI KAWASAN CENGKARENG JAKARTA BARAT DAN BANJIR DI KAWASAN KELAPA GADING JAKARTA UTARA - Laksmi Gondokusumo Siregar (Environmental Research Center (PPLH) of Udayana University, 2009)
To inhabit the earth is a blessing and a responsibility that given by The Almighty God to us as human beings. Accordingly, this paper explores deep thoughts which was necessary to be understood by human who exist on earth. An ethical based behavior and an understanding about thoughts which potentially change natural environment to artificial one was becoming significant to be investigated for the sake of human being in general. When there was a development conducted on one area, it would cause some impacts which should previously cautiously calculate. The impacts would affect far in the future, so the area as an architectural creation should had some thoughtful aspects inside its development. Therefore, the architectural design would also maintained and made plan for an steady environment which would keep the city away from floods or any other disasters.